(untitled) (Conference Zone, 2022)
Alkaloids have a wide range of effects on humans and animals, and it is very expensive to obtain them artificially. Therefore, it is important to identify medicinal plants that contain alkaloids. This article gives you a brief overview on alkaloid-containing plants and their training technologies.